Salvage right - Lee, Sharon, 1952-; Miller, Steve, 1950 July 31- (Lee, Sharon, 1952- Liaden universe, 2023)
"A door never closes, but a window opens . . . With origins in the Old Universe, the malevolent, acquisitive intelligence of Tinsori Light sought to infect others with itself, and send those agents out into the wide new universe to infect even more. For centuries, two heroes stood between Tinsori Light and the vulnerable universe-Light Keepers Jen Sin yos'Phelium and Lorith of the Sanderat. Just when it seemed that they-merely human-must fail, Tinsori Light, enfeebled by aged systems, succumbed to the stress of a unique spatial event-and died, leaving the station a shell. Luckily, the light keepers have back-up. A mismatched team of arcane specialists are on-station, working non-step to preserve the Light, build trustworthy systems, and open the refurbished station for business. In fact, ships are already incoming, and it becomes a matter of urgency to sort friend from foe. In particular, the Lyre Institute wishes to acquire Tinsori Light, and will do anything, spend anyone, to achieve that goal"--